1919 Colo. Sess. Laws 416 - 17, Foreign-Born Unnaturalized Citizens, § 1 - (:unkn) unknown (General Publisher, 1919)
Prohibited noncitizens from owning or possessing any shotgun, rifle, pistol or firearm of any kind; violators subject to fine, imprisonment, confiscation of weapon.
--
Keywords: POSSESSION - DANGEROUS PERSONS